Characteristics of late reformation and petroleum prospect of Carboniferous strata in the Bayanhot Basin, N. China. Issue 10 (17th July 2022) - Zhao, Hongge; Liu, Chiyang; Zhou, Yijun; Shao, Xiaozhou; Wang, Jianqiang; Peng, Zhichao; Huang, Lei; Ruan, Zhengzhong; Guo, Hui; Fu, Xinhui; Li, Ya'nan
Abstract : The Bayanhot Basin is located at the intersection of the Alxa Block, Ordos Basin, and Corridor Transitional Zone. Although the Carboniferous palaeo‐sedimentary and tectonic features are of great significance in discovering the scientific issues of the influential range of the Qinlin‐Qilian Ocean and palaeo‐Asian Ocean and the relationship of the North China Block and Alxa Block, as well as in evaluating hydrocarbon prospects, it is difficult to restore the Carboniferous features because of intense late reformation. It is necessary to systematically discuss the late reformation characteristics. It is shown in this paper that Carboniferous strata have mainly experienced two extensive tectonic movements during the Late Hercynian–Indosinian and Yanshanian periods and had four reformation types: structural compression, uplift to erosion, superimposed and deep burial, and thermodynamic reformation, based on comprehensive analysis of seismic profiles, wells, aeromagnetic data and tectonic characteristics of the surrounding regions. Carboniferous strata were partly eroded by the compressional folding during Late Hercynian–Indosinian movement, and were forcefully eroded by thrusting and uplift during Yanshanian movement, especially movement in the Late Jurassic, which determined the present thickness of the Carboniferous strata. The deep overlap of the overlying Jurassic, Lower Cretaceous, Palaeogene, and Neogene rocks in different areas was beneficial to the maturation of Carboniferous source rocks. The magmatic rocks exposed by well drilling and shallow aeromagnetic anomaly belts show heating reformation, which accelerated the maturation of source rocks to some extent. The total strength of the Carboniferous late reformation was stronger in the western area than in the eastern area and greater in the northern area than in the southern area. The multiple periods and various types of reformation were closely related to the regional closure of the Palaeo‐Qinling‐Qilian Ocean in the south, Palaeo‐Asian Ocean, and Mongolia–Okhotsk Ocean in the north and the subduction of the Palaeo‐Pacific Plate in the east. The Carboniferous strata in eastern and southern basins will be the prospective favourable areas for the petroleum exploration. Abstract : Carboniferous strata have mainly experienced two extensive tectonic movements during the Late Hercynian‐Indosinian and Yanshanian periods and had four reformation types of structural compression, uplift to erosion, superimposed and deep burial and thermodynamic reformation. The strata in eastern and southern basin will be the favorable areas for petroleum exploration.